Problems of the Articulation between Phenomenology and Hermeneutics in J.-L. Marion’s work, in dialogue with C. Romano’s proposal - Roggero, Jorge Luis (Logos. Anales del Seminario de Metafísica, 2020)
This article aims to examine the way in which the phenomenology of donation can achieve a successful articulation with hermeneutics. Following the indication given by Marion himself, through a comparison of his approach with that of Claude Romano, it is possible to establish to what extent the Marionian proposal is capable of responding to the hermeneutical and phenomenological demands that the articulation requires.